Behavioural Responses to Taxes and Optimal Taxation of Top Labour Incomes in Croatia - Rubil, Ivica; Ledić, Marko (Panoeconomicus, 2025)
We use a model of optimal labour income taxation and tax records data to determine the optimal marginal tax rate for top labour income earners in Croatia in the period 2014–2021. Behavioural responses to taxation through labour supply and tax evasion, captured by the elasticity of taxable income, are estimated based on several tax reforms. Responses through international migration are also considered. In 2021, for most combinations of the relevant parameters, the optimal top marginal rate of personal income tax is higher than the actual rate. Also, for most parameter combinations, the reductions in the top marginal rate over 2014–2021 cannot be justified from the optimal taxation perspective. Further reductions in the top rate can be justified for only a few parameter combinations. While the literature on the elasticity of taxable income and the optimal taxation of top earners was focused on Western Europe and the US, this paper contributes by considering a Southeast European country. JEL: H21, H31